2021
DOI: 10.1002/pssb.202100317
|View full text |Cite
|
Sign up to set email alerts
|

The Two Types of Oxygen Interstitials in Neutron‐Irradiated Corundum Single Crystals: Joint Experimental and Theoretical Study

Abstract: Corundum (α‐Al2O3) is a technologically important material and, in particular, widely used in optical applications such as luminescent radiation dosimeters, cryogenic scintillators, and is being considered as a promising candidate for windows in future fusion reactors. Its optical and mechanical properties are controlled by the presence of radiation‐induced (in particular, by fast neutrons) defects. Herein, the thermal stability and recombination kinetics of primary anion Frenkel defects—the F and F + electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is well known that an alternative mechanism for annealing radiation-induced F -type defects in oxides is the recombination of oxygen vacancies with interstitial oxygen, the diffusion of which becomes possible when the crystal is heated [ 48 , 49 , 50 ]. Previously, the authors of [ 51 ] showed that in zirconium oxide irradiated with neutrons (E > 0.1 MeV), the diffusion of interstitial oxygen becomes possible at temperatures above 500–600 K. In the samples studied by us, a decrease in the concentration of F + centers is observed at lower temperatures of 375–550 K, which testifies in favor of the proposed mechanism for the destruction of F + centers associated with their ability to capture the charge carriers released from traps that cause TL peaks.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that an alternative mechanism for annealing radiation-induced F -type defects in oxides is the recombination of oxygen vacancies with interstitial oxygen, the diffusion of which becomes possible when the crystal is heated [ 48 , 49 , 50 ]. Previously, the authors of [ 51 ] showed that in zirconium oxide irradiated with neutrons (E > 0.1 MeV), the diffusion of interstitial oxygen becomes possible at temperatures above 500–600 K. In the samples studied by us, a decrease in the concentration of F + centers is observed at lower temperatures of 375–550 K, which testifies in favor of the proposed mechanism for the destruction of F + centers associated with their ability to capture the charge carriers released from traps that cause TL peaks.…”
Section: Resultsmentioning
confidence: 99%
“…E. Kotomin et al, V. Gusakov et al, and R. Maji et al used ab initio calculations to describe the thermal stability and recombination kinetics of primary anion Frenkel defects À the F and F þ electronic centres and oxygen interstitials À in fast-neutronirradiated α-Al 2 O 3 single crystals, [1] formation and diffusion of intrinsic defects in bulk and monolayer MoS 2 , [2] and the interaction of grain boundaries (GB) with inherent defects and/or impurity elements in multi-crystalline Si, [3] respectively. The co-existence of two types of interstitialsneutral O atoms and negatively charged O ionsin α-Al 2 O 3 has been demonstrated for the first time.…”
mentioning
confidence: 99%